Insolation of the premise as a factor of vitamin d producing radiation in bedridden patient (Environment & Health, 2022)
Objective: We substantiated the conditions of the use of premise insolation to organize a prophylactic irradiation of human skin in order to ensure a synthesis of the required doses of vitamin D.Materials and methods: Using geometric methods for constructing shadow mask of a light slot of the window according to the State Standard B V.2.2-27: 2010, we calculated a duration of the insolation at 63 points in the conditional model premise with an open half of the window on a horizontal surface at a height of 0.50 m above the floor at different heights of the sun in the warm months of the year (May–September). The dimensions of a conditional bed were 0.84 m width and 1.94 m length. The required exposure time for bedridden patient in the sunspot to receive a prophylactic dose of vitamin D (1000 IU) into organism was calculated by the A.R. Webb, & O. Engelsen model (2020).Results: The study determined the duration of insolation with the open half of the window of the model premise on a parallel plane in the warm months of the year (May - September) at a height of 0.50 m from the floor at points located on the coordinate grid with a step of 0.50 m and at the average values of the sun standing height which forms a sunspot. At the same time, the duration of the insolation at the points near the window ranged from 1 hour 10 minutes to 3 hours 38 minutes on some above mentioned months.The results of the analysis on the limitations of the application of the model by A.R. Webb and O. Engelsen (2020) for the determination of the required duration of the human body indoor insolation to achieve the effective ultraviolet B (UVR) doses for vitamin D production equivalent to the oral intake of the recommended prophylactic doses of vitamin D are also presented in the study.Conclusions: In the insolated premise on a clear day of the warm months of the year (May - September), it is in principle possible to organize the exposure of the part of the skin of a person lying on a bed in a sunspot, formed by an open window, with the required duration and intensity of UVR B that provide a bioeffective dose equivalent to the oral intake of the prophylactic dose of vitamin D (1000 IU).
Keywords: sunlight; solar charts; insolation of the premise; vitamin D; bioefficiency of ultraviolet radiation of the sun